Quranic Features of Healing and Treatment: An Indexing of Quranic (Medical Instructions) Verses - Abdul Rahman Hussein Obeid; Adnan Mohamed Yusoff; Mohd Zohdi Mohd Amin; Syed Ahmad Tarmizi; Syed Omar (European Scientific Institute, 2024)
Non-Indexed Publication